Novel design strategy for GaAs‐based solar cell by application of single‐walled carbon nanotubes topmost layer. Issue 8 (23rd April 2020) - Mitin, Dmitry M.; Bolshakov, Alexey D.; Neplokh, Vladimir; Mozharov, Alexey M.; Raudik, Sergei A.; Fedorov, Vladimir V.; Shugurov, Konstantin Yu.; Mikhailovskii, Vladimir Yu.; Rajanna, Pramod M.; Fedorov, Fedor S.; Nasibulin, Albert G.; Mukhin, Ivan S.
Abstract: Attempts to improve solar cells efficiency touch all its constituents and are directly related to their fabrication protocols. While the most promising material platform for high efficiency photovoltaic devices is still III‐V semiconductors, introduction of novel materials like single‐walled carbon nanotubes (SWCNTs), which are characterized by unique combination of conductivity and transparency, might greatly yield the device performance. Here, for the first time, we present the results of the fabrication and characterization of a thin‐film GaAs solar cell with a SWCNT top contact. We examine the contact between the SWCNT film and the semiconductor structure by means of the optical and electron beam‐induced current techniques. The fabricated device demonstrates better performance, that is, increased power conversion efficiency from 10.6% to 11.5% when compared to the cell with the traditional metal contact grid, stemming from the enhanced photocurrent collection efficiency and low parasitic light absorption in the emitter layer. We envision future prospects to exploit the multifunctionality of the SWCNTs in fabrication of highly efficient photovoltaic devices including flexible solar cells. Abstract : We present the results of the fabrication and characterization of GaAs solar cell with a SWCNT top contact. We examine the contact between the SWCNT film and the semiconductor structure by means of the optical and electron beam‐induced current techniques. The fabricated device demonstrates increased power conversion efficiency from 10.6% to 11.5% when compared to the cell with the traditional metal contact grid, stemming from the enhanced photocurrent collection efficiency and low parasitic light absorption in the emitter layer.